Adaptive Fault-Tolerant Control for Attitude Tracking of a Carrier-Based Aircraft Subject to Actuator Faults - Liu, Simin; Zheng, Zewei; Zhu, Bing; Guan, Zhiyuan (IEEE transactions on aerospace and electronic systems, 2024)
This article presents a fault-tolerant attitude tracking control for carrier-based aircraft subject to actuator faults. The proposed controller adopts nonlinear dynamic inversion (NDI) to ensure asymptotic attitude tracking for the fault-free attitude system and employs \mathcal{L}_{1} piecewise constant adaptive law to compensate for errors caused by actuator lock-in-place (LIP) faults. Theoretical analysis indicates that by reducing the sampling time of the adaptive law, the performance difference bounds of the closed-loop \mathcal{L}_{1} adaptive system and the closed-loop reference system can be adjusted to be arbitrarily small. The fault-tolerant performance of the proposed method is supported by data acquired from flight tests.